Short term performance evaluation of a rural road embankment with different reinforcement constructed on soft soil pertaining to vertical settlement - Abdurahman, Mohamad Nizar (2005)
Construction of roads on soft soil is common in Southern part of Peninsular Mal?ysia especially on its coastal area. Many problems were faced during road constructions when done on soft soils. They are subjected to instability and massive primary and long term consolidation settlements when subjected to even moderate load increases. Most pavements constructed in such a difficult grounds are improved with the use of geotextiles. This research is carried out to get a correlation between the frequency of standard truck loading with the settlement for road embankment constructed on soft soil using different reinforcements. Two (2) types of geotextiles are used. They are Rawell Geosynthetic Clay Liner(RGCL) and Woven Geotextiles(WG). Continuous monitoring and evaluation are conducted on three (3) different full-scale road embankment models at Research Centre for Soft Soil (RECESS). All sections are loaded using 5 ton truck during Static and Dynamic loading. The performance of road in every sections are monitored and evaluated. From findings, it shows that for frequency of 50 passes per day the settlements for GCL are 0.030 m and 0.063 m, and for WG are 0.168 m and 0.082 m for both 0 m and 0.5 m excavated sections respectively. For frequency of 100 passes per day the settlements for GCL are 0.026 m and 0.068 m, and for WG are 0.168 m and 0.088 m for both 0 m and 0.5 m excavated sections respectively. From the data, we can see that the performance of GCL is better compared ~o WG for the 0 m and 0.5 m excavated sections. The values of settlement in every sections are also increased when the frequency of dynamic load is increased.